ANALISA PERBANDINGAN R DAN C SEBAGAI PENGGANTI L ( BALLAST ) PADA FLUORESCENT ATAU LAMPU TL ( LAMPU TABUNG ) - admin, Yasri . (Journal of Electrical Engineering, Energy, and Information Technology (J3EIT), 2013)
Passive elements in electricity there is three kind of resistances (R), Induktance (L), and capacitance (C). on the study of resistif properties of the resistor and the capasitor is used to ignite the lamp TL becaue in general elements commonly used to light the lamp TL is simply L ( Ballasts ). For elements of R and C that stands on its own is very rarely used us reactance on the line voltage. Keyword : Ballast, Resistor, Kapasitor